Sychentia hainanensis sp. n., the first record of the genus from China, with notes on the morphology and biogeography (Hemiptera: Cicadellidae) - Wei, Cong; Zhang, Yalin (Zootaxa, 2013)
Sychentia hainanensis sp. n. is described and illustrated from Hainan Island, representing the first record of the genus from China and the second known species of the genus. The morphology and biogeography of the genus Sychentia Wei & Webb and related genera are discussed.